2022
DOI: 10.1111/rode.12968
|View full text |Cite
|
Sign up to set email alerts
|

Do farmers get a greater return from selling their agricultural products through e‐commerce?

Abstract: E-commerce allows farmers to cut out intermediaries and sell agricultural products to consumers directly. This raises the question of whether farmers get a greater return when they use e-commerce to sell their products than when they use conventional marketing channels (i.e., intermediaries). To answer this question, we collected rural household data on sales of agricultural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Overall, the empirical research in this paper confirms that the E-commerce development policy has a significant, positive, and sustainable impact on high-quality agricultural development. This not only dramatically enriches the literature on the impact of e-commerce [8][9][10][11] and the development of agricultural e-commerce [21,43], providing empirical support for the rationality and effectiveness of various forms of e-commerce to assist agriculture, but also provides empirical evidence for local governments to use E-commerce to enable high-quality agricultural development. In addition, this study also found that for cities with good primary conditions for development, E-commerce development has a more significant positive impact on high-quality agricultural development.…”
Section: Plos Onementioning
confidence: 64%
See 2 more Smart Citations
“…Overall, the empirical research in this paper confirms that the E-commerce development policy has a significant, positive, and sustainable impact on high-quality agricultural development. This not only dramatically enriches the literature on the impact of e-commerce [8][9][10][11] and the development of agricultural e-commerce [21,43], providing empirical support for the rationality and effectiveness of various forms of e-commerce to assist agriculture, but also provides empirical evidence for local governments to use E-commerce to enable high-quality agricultural development. In addition, this study also found that for cities with good primary conditions for development, E-commerce development has a more significant positive impact on high-quality agricultural development.…”
Section: Plos Onementioning
confidence: 64%
“…It is considered a practical solution to the urban-rural gap [ 9 ]. The sale of agricultural products through E-commerce improves the price transparency of agricultural products, reduces mediators, and improves market efficiency [ 10 ]. It has been widely used in developing countries such as India, Indonesia, and China, gradually expanding from large cities to small cities and villages [ 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation in rural e-commerce can effectively enhance the economic benefits of farming households [65,66]. This is achieved through various channels, including increasing employment opportunities and agricultural income, which significantly improves the resilience of farming households [67]. Rural e-commerce can increase the employment opportunities of farmers and help them diversify the risks of family production and operation by improving non-farm economic income [68].…”
Section: Mediating Role Of Economic Gainsmentioning
confidence: 99%
“…Efficient distribution of agricultural products plays a pivotal role in agricultural operations, serving as a critical component of the agricultural value chain that directly influences farmers' income and market stability. With the advent of e-commerce, agricultural ecommerce has forged new sales avenues for farmers, effectively mitigating the challenges of information asymmetry and market volatility in traditional sales channels [1,2]. The advent of live streaming e-commerce has revitalized the distribution and sale of agricultural products within the agricultural value chain through its distinctive real-time interactive and dynamic display features [3].…”
Section: Introductionmentioning
confidence: 99%